ASPECTOS ETOLÓGICOS E LONGEVIDADE DE Diaeretiella rapae M’Intosh, 1855 (HYMENOPTERA: APHIDIIDAE) - Bueno, Vanda Helena Paes; Souza, Bernadete Maria de (REVISTA DE AGRICULTURA, 2015)
ASPECTOS ETOLÓGICOS E LONGEVIDADE DE Diaeretiella rapae M’Intosh, 1855 (HYMENOPTERA: APHIDIIDAE)